Pattern of Investment and Domestic Product in India : Trends and Inter-Relation-1950-51 to 1977-78 - Planning Commission (Planning Commission, 1981)
This report examines the relationship between investment and GDP in India from 1950-51 to 1977-78, analyzing growth trends, sectoral contributions, and investment elasticity. GDP grew at an average rate of 3.7% per annum, with the secondary sector leading at 5.3% and the primary sector lagging at 2.6%. Investment increased at 5.8% annually, predominantly in the secondary sector, while the transport and real estate sectors grew modestly. The GDP elasticity with respect to investment was 0.41, indicating moderate responsiveness. Findings reveal structural shifts from the primary to secondary and transport sectors and underscore the need for integrated planning strategies to enhance economic growth in India.
Government of India Planning Commission (UNDP Transport Policy Planning Projects)
Government of India Planning Commission (UNDP Transport Policy Planning Projects)
Keywords: Investment Patterns; Gross Domestic Product; India; Sectoral Growth; Capital Formation; Economic Planning; Primary Sector; Secondary Sector; Elasticity of GDP; Structural Shift